Seed priming with SNP improves the performance of aged pumpkin (Cucurbita pepo L.) seeds under drought stress - Hossein Reza Rouhi; َAli Moradi; Maryam Saman; Yasin Mohammadi; Alireza Shahbodaghlo (علوم و فناوری بذر ایران, 2019)
In order to investigate the effect of sodium nitroprusside (NO donor) on improvement of aged pumpkin seeds under drought stress, a factorial experiment was carried out based on completely randomized design with three replications in Bu-Ali Sina University, Hamedan, Iran. Seed priming with different concentrations of sodium nitroprusside including 0 (hydropriming), 25, 50 and 75 µM in drought stress levels (0, -0.2, -0.46 and -0.6 MPa) was performed. Germination percentage, germination rate, seed vigor, seedling length, soluble carbohydrates, soluble proteins, memberane electrical conductivity, malondialdehyde content and antioxidant enzymes activity (catalase, ascorbate peroxidase and superoxide dismutase) were evaluated. The results showed that seed priming with different concentrations of sodium nitroprusside mitigated significant decrease of germination parameters of aged seeds under drought stress. At -0.6 MPa, seed priming with 75 µM of sodium nitroprusside increased germination rate, vigor index , soluble carbohydrates and proteins 25, 214.1, 90.8, 117.1%, as well as the activity of catalase, superoxide dismutase and ascorbate peroxidase increased by 34, 14.5, 41.4% in comparison to control, respectively. Therefore, seed priming with sodium nitroprusside specialy with 75 µM is suggested for aged pumpkin seeds by decreasing oxidative stress due to drought stress.